Enhancing Gross Motor Skills In Early Childhood Through Group Play - Yosi Amanda; Dwieka Aprinnisa, Rizka (Jurusan Pendidikan Islam Anak Usia Dini, 2024)
This research is entitled Gross Motor Ability through Jumping Games in Children in Group B at the Pembina State Kindergarten, Kutaraya Village, Kayu Agung District, Ogan Komering Ilir Regency. This community service program is based on the collaboration of Real Work Lecture students at Raden Fatah State Islamic University, Palembang. This research aims to develop children's gross motor skills in playing and focusing on their memory. This research method is descriptive qualitative. The technique used in this research is an observation and documentation type technique. The technique and documentation show that jumping activities according to the colors mentioned can improve children's gross motor skills and focus in playing at the Pembina State Kindergarten, Kutaraya Village, Kayu Agung District, Ogan Komering Ilir Regency, Year Teachings 2023/2024